ChemInform Abstract: Photocatalytic Synthesis of Oxetane Derivatives by Selective C—H Activation. Issue 10 (March 2015) - Ravelli, Davide; Zoccolillo, Matteo; Mella, Mariella; Fagnoni, Maurizio
Abstract The novel photochemical generation of α‐oxy radicals from oxetanes and subsequent trapping by electron poor olefins renders possible the preparation of various novel 2‐substituted oxetane derivatives.